ECONOMIC ANALYSIS TO ESTIMATION THE IMPORTED INFLATION IN AGRICULTURAL SECTOR IN IRAQ FOR THE PERIOD 1990-2019 - ALL Iessa, Doaa E. S.; Al-Badri, Basim H. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was aimed to measure and evaluation the imported inflation in agricultural sector in Iraq. Moreover, studying and analyzing the most important factors affecting it during 1990-2019. This research reached to- via results of unit root test- that all variables were non-stationary at the level, but all of them were stationary at the difference. The research conclude- through significance of parameters of agricultural trade openness in the model. That the imported inflation can be rising in agricultural sector after the trade liberalization and interring to WTO and increasing of dumping policy in agricultural products, whereas found when measuring the imported inflation the high dependency of agricultural sector in Iraq on the imported equipment’s and agricultural and foods products, and influence of rising of global prices in it especially after 2003.The research recommended to controlling the rates of imported inflation by using studied import policies and not allowed of randomized of importing agricultural products, the research recommends also to reduce the impact of dumping policy in agricultural products.